1998
DOI: 10.1183/09031936.98.12010013
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of bronchial hyperresponsiveness and asthma in ice hockey players

Abstract: The prevalence of asthma was studied in a ice hockey team compared with both a floor ball team and the Swiss population. Lung function, bronchial hyperresponsiveness to methacholine, asthma symptoms and exercise-induced asthma were measured in a cross-sectional prospective study. A positive response to the methacholine bronchial provocation test was found in 34.6% of the ice hockey players and 20.8% of the floor ball players (Swiss population 16.4%). The provocative dose causing a 20% fall in the forced expira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 21 publications
4
41
4
Order By: Relevance
“…Asthma has a high prevalence in European countries, about 10-12% of the childhood population. The prevalence of EIA is also much higher in subjects who take part in sport at elevated workloads in cold environments: ice hockey players (21%) [33], cross country skiers (31%) [34], and figure skaters (55%) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Asthma has a high prevalence in European countries, about 10-12% of the childhood population. The prevalence of EIA is also much higher in subjects who take part in sport at elevated workloads in cold environments: ice hockey players (21%) [33], cross country skiers (31%) [34], and figure skaters (55%) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Two skiers had BHR without symptoms and 17 had symptoms, but no BHR. Leuppi et al [7] found that 35% of Swiss ice hockey players had BHR, but clinical asthma was diagnosed in 19% and exercise-induced bronchospasm (EIB) in 11% of them. The respective figures for BHR, clinical asthma and EIB were lower in floor ball players: 21%, 4.2% and 4.2%.…”
Section: Occurrence Of Bronchial Hyperresponsivenessmentioning
confidence: 99%
“…In summer sport events, the prevalence ranges 3.7-22.8%, as reviewed by Helenius and Haahtela [1]. In winter sport events, the occurrence is even higher, ranging 2.8-54.8% (table 1) [2][3][4][5][6][7][8]. A total of 17% of 253 Finnish elite summer sport athletes used asthma medication, most commonly inhaled b 2 -agonists [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three groups (G1, G2, G3) were formed on a basis of percentage of diminution in the Forced Expiratory Volume in 1 Second (FEV 1 ) after Exercise-Induced Bronchospasm (EIB) test on day zero (D 0 ) (Durand et al, 2005;Rundell and Jenkinson, 2002;Weiler and Ryan, 2000;Leuppi et al, 1997;Mannix et al, 1996). (Fig.…”
Section: Constitution Of Experimental Groupsmentioning
confidence: 99%